Carbon quantum dots as a dual platform for the inhibition and light-based destruction of collagen fibers: implications for the treatment of eye floaters. Issue 6 (27th April 2021) - Barras, Alexandre; Sauvage, Félix; de Hoon, Inès; Braeckmans, Kevin; Hua, Dawei; Buvat, Gaëtan; Fraire, Juan C.; Lethien, Christophe; Sebag, J.; Harrington, Michael; Abderrahmani, Amar; Boukherroub, Rabah; et al.
Abstract : Fibrillation of collagen I is prevented most strongly by positively charged CQDs and pulsed-laser illumination destroys collagen aggregates and vitreous opacities. Abstract : Common in myopia and aging, vitreous opacities arise from clumped collagen fibers within the vitreous body that cast shadows on the retina, appearing as 'floaters' to the patient. Vitreous opacities degrade contrast sensitivity function and can cause significant impairment in vision-related quality-of-life, representing an unmet and underestimated medical need. One therapeutic approach could be the use of versatile light-responsive nanostructures which (i) interfere with the formation of collagen fibers and/or (ii) destroy aggregates of vitreous collagen upon pulsed-laser irradiation at low fluences. In this work, the potential of positively and negatively charged carbon quantum dots (CQDs) to interfere with the aggregation of type I collagen is investigated. We demonstrate that fibrillation of collagen I is prevented most strongly by positively charged CQDs (CQDs-2) and that pulsed-laser illumination allowed to destroy type I collagen aggregates and vitreous opacities (as obtained from patients after vitrectomy) treated with CQDs-2.